Rancangan dan Evaluasi Usability Pada Aplikasi Website Media Pembelajaran Cyberbullying Menggunakan Metode Gamifikasi - Abimanyu Manusakerti; Merlinda Wibowo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Cyberbullying is bullying act carried out on social media to cause harm the victim. The potential for cyberbullying is very high among teenagers. This is due to high frequency of using social media, increasing cases of cyberbullying, and the lack of education about cyberbullying. Cyberbullying education has been carried out using digital literacy educational activities using digital literacy only focus on introducing and preventing cyberbullying in the form of seminars or lectures. However, using this method has many shortcomings, for example someone easily forgets the material presented and gives less space to develop creativity. Interactive education is needed to increase motivation to learn about cyberbullying. The gamification method is very suitable to be applied in learning because the gamification method involves game elements such as points, leaderboards, badges, challenges, and achievements. In addition to using the gamification methods, visual media such as images and animation video is also suitable for learning. This research utilizes gamification-based learning and visual media to deliver the material as a prototype application for cyberbullying learning sites. This research aims to provide education and increase motivation to learn about more interactively cyberbullying. This research involved 42 respondents with a range of ages between 12-21 years. This research will use System Usability Scale (SUS) to evaluate the prototype's usability. The usability score from the prototype in this research is 77.8, meaning the prototype is acceptable to use.